2016
DOI: 10.1155/2016/3810175
|View full text |Cite
|
Sign up to set email alerts
|

Poly(lactic-co-glycolic) Acid-Chitosan Dual Loaded Nanoparticles for Antiretroviral Nanoformulations

Abstract: Poly(lactic-co-glycolic acid) (PLGA) chitosan (CS) coated nanoparticles (NPs) were loaded with two antiretrovirals (ARVs) either lamivudine (LMV) which is hydrophilic or nevirapine (NVP) which is hydrophobic or both LMV and NVP. These ARVs are of importance in resource-limited settings, where they are commonly used in human immunodeficiency virus (HIV-1) treatment due to affordability and accessibility. NPs prepared by a water-oil-water emulsion and reduced pressure solvent evaporation technique were determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 36 publications
0
14
1
Order By: Relevance
“…Studies on aptamer-based enhanced drug delivery have been reported for prostate cancer and lymphoblastic leukemia cells [201]. With this purpose, for HIV therapy, nanoparticles successfully loaded with the antiretroviral (ARV) drugs efficiently inhibited HIV-1 infection [202,203]. These results showed the benefit of the nanoparticles’ application to delivery of antiviral drugs to improve its bioavailability.…”
Section: Perspectivesmentioning
confidence: 99%
“…Studies on aptamer-based enhanced drug delivery have been reported for prostate cancer and lymphoblastic leukemia cells [201]. With this purpose, for HIV therapy, nanoparticles successfully loaded with the antiretroviral (ARV) drugs efficiently inhibited HIV-1 infection [202,203]. These results showed the benefit of the nanoparticles’ application to delivery of antiviral drugs to improve its bioavailability.…”
Section: Perspectivesmentioning
confidence: 99%
“…The physicochemical properties of emulsions, such as the droplet size, zeta potential and CF, affect their stability and usability . The physicochemical properties of the HMEs are listed in Table .…”
Section: Resultsmentioning
confidence: 99%
“…In this method the change in conductivity was measured after each ml of addition of TPP solution to the nanoparticle solution. [30] Stability of Prepared Single and Dual Loaded NPs.…”
Section: Entrapment Efficiency (%Ee)mentioning
confidence: 99%